The use of mass media as a didactic strategy in the teaching of English as a foreign language - Music and songs - Mideros, Diego (School of Education, UWI, St. Augustine, 2008)
This project was inspired by the influence of the mass media on society today. The main objective was to introduce a meaningful and communicative environment in the classroom by applying authentic material from the mass media to the teaching of English to fifth grade students in the city of Bogotá, Colombia. The use of mass media allows teachers to expose students to authentic English instead of teaching from traditional textbooks that may be mundane from the students' point of view. Music and songs facilitated work on five different aspects: vocabulary, grammar, listening, speaking, pronunciation, and communication. The material selected gave the students patterns and tools to communicate in English
Keywords: Language education; English as a foreign language; Foreign languages; Mass media; Teaching techniques; Colombia